Desarrollo del patrón de medición de potencia y energía para el Instituto Costarricense de Electricidad - Castañeda-García, Ión Veiko (Instituto Tecnológico de Costa Rica, 2002)
This paper reports a proyect performed by a student from Instituto Tecnológico de Costa Rica, which was realized at the Metrology Laboratory of Costarrican Electricity Institute. The project objective was the traceability of the electric power and energy measurement primary standard, by means of a high precision digital multimeter until electric DC voltage primary standard, according the design reported on the paper of the engineers Bryan C. Waltrip and Nile M. Oldham from National Institute of Standards and Technology (NIST) of United States of America (1997). The established system is used to measure energy and average power based on three AC voltage measurements for any angle of power factor between 0° and 60°. It is reported there were differences in determinations based on built circuit performance, which was constructed based in locally available materials (that not coincide with those specified in the original design). Report concludes that major work should necessary with suitable materials in order to get the remaining objectives established in the project. The author thanks the valuable cooperation gotten from the designer engineer Bryan C. Waltrip, about the construction of the circuit.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Electrónica, 2002.
Keywords: Trazabilidad; Circuitos; Corriente; Operaciones; Voltaje; Diagramas